A thermocatalytic perovskite-graphene oxide nanofiltration membrane for water depollution. (October 2022) - Bortot Coelho, Fabricio E.; Nurisso, Federica; Boffa, Vittorio; Ma, Xianzheng; Rasse-Suriani, Federico A.O.; Roslev, Peter; Magnacca, Giuliana; Candelario, Victor; Deganello, Francesca; La Parola, Valeria
Abstract: A novel nanofiltration membrane, whose active layer consists of 98.6 wt% of a thermocatalytic perovskite with composition Sr0.85 Ce0.15 FeO3-δ (CSF), 1.0 wt% of graphene oxide (GO), and 0.4 wt% of a humic acid-like (HAL) crosslinker, was deposited over a commercial flat-sheet polyethersulfone support with good reproducibility by a simple 1-step coating procedure. The synergistic coupling of CSF and the crosslinked GO resulted in an improved catalytic activity for bisphenol A (BPA) abatement as a model pollutant. The thermocatalytic CSF/GO/HAL (GOT) membrane was tested in a nanofiltration crossflow apparatus with a model BPA solution and with a real urban wastewater treatment plant effluent. Its performances were compared with those of a HAL crosslinked GO (GOHAL) reference membrane. The GOT membrane presented high rejection towards BPA, antifouling properties, and stability under the filtration conditions. Moreover, when compared to the GOHAL reference, the thermocatalytic GOT membrane was able to reduce the concentration of BPA and the total organic carbon in the feed during filtration. Hence, the GOT membrane appears to have high potential in water treatment due to its multifunctional characteristics, which include molecular sieving, thermocatalytic oxidation of organic pollutants, and self-cleaning properties. Additionally, the membrane material showed no significant toxicity to the aquatic model organisms Raphidocelis subcapitata, Aliivibrio fischeri, and Daphnia magna at concentrations below 50 ppm.